Renal Interstitial Invasion by Group A Streptococcus: A Rare Presentation - Francis Lomanta; Shankar Upadhyayula (Case Reports in Infectious Diseases)
We report the case of a 5-year-old who had interstitial invasion of his kidneys with group A Streptococcus (GAS). Glomeruli and tubules were relatively preserved. He recovered from this event and was admitted a couple of months later with dilated cardiomyopathy needing a heart transplant. To our knowledge, this is the first reported case of direct invasion of renal interstitium by GAS.